EFFECTS OF LAMINA ORIENTATION ON UNIAXIAL BUCKLING LOAD OF COMPOSITE PLATES - ABDULLA , KAREEM ABDULGHAFOUR; EZDEEN , SAFEEN YASEEN (Journal of Duhok University, 2023)
The purpose of this research is to look at the buckling behavior of axially loaded, symmetrical laminated composite rectangular plates with simple support boundary conditions all around. In this work, balance equations based on Classical Plate Theory (CPT) produced from Kirchhoff assumptions are used to present formulas that determine the critical buckling load for orthotropic plates step by step. The formulas that provide the critical buckling load for thin composite plates with simple support on all four sides under a uniaxial compression force are presented. For the laminated rectangular composite plate constructed using different fiber orientations of N orthotropic layers employed in analytical solution, the required formulas are supplied. The numerical results from the ANSYS ACP Workbench analysis program and the analytical results produced with the MATLAB application were compared. Different methods employed by other studies when modifying some design components such as modulus ratio and aspect ratio(a/b) have shown that the aspect ratio is inversely proportional to the buckling. Comparisons between various plate fiber directions, layer thicknesses, plate dimensions, and composite plates were made. Higher resistance to buckling and the largest buckling load are obtained by orienting the laminate at a 90° angle.